Maternal and perinatal outcomes by planned place of birth among women with low-risk pregnancies in high-income countries: A systematic review and meta-analysis. (July 2018) - Scarf, Vanessa L; Rossiter, Chris; Vedam, Saraswathi; Dahlen, Hannah G; Ellwood, David; Forster, Della; Foureur, Maralyn J; McLachlan, Helen; Oats, Jeremy; Sibbritt, David; Thornton, Charlene; Homer, Caroline S E
Highlights: The review compared studies of births planned in hospital, birth centres and at home. A specific instrument appraised quality of evidence in research on birth setting. Studies varied in design, location, context and definition of key terms. High quality studies found no statistically significant difference in infant mortality by setting. Women have higher odds of normal vaginal birth at home or in birth centres. Abstract: Background: The comparative safety of different birth settings is widely debated. Comparing research across high-income countries is complex, given differences in maternity service provision, data discrepancies, and varying research techniques and quality. Studies of births planned at home or in birth centres have reported both better and poorer outcomes than planned hospital births. Previous systematic reviews have focused on outcomes from either birth centres or home births, with inconsistent attention to quality appraisal. Few have attempted to synthesise findings. Objective: To compare maternal and perinatal outcomes from different places of birth via a systematic review of high-quality research, and meta-analysis of appropriate data (Prospero registration CRD42016042291). Design: Reviewers searched CINAHL, Embase, Maternity and Infant Care, Medline and PsycINFO databases to identify studies comparing selected outcomes by place of birth among women with low-risk pregnancies in high-income countries. They critically appraised identified studies using an instrument specific to birth place research and then combined outcome data via meta-analysis, using RevMan software. Findings: Twenty-eight articles met inclusion criteria, yielding comparative data on perinatal mortality, mode of birth, maternal morbidity and/or NICU admissions. Meta-analysis indicated that women planning hospital births had statistically significantly lower odds of normal vaginal birth than in other planned settings. Women experienced severe perineal trauma or haemorrhage at a lower rate in planned home births than in obstetric units. There were no statistically significant differences in infant mortality by planned place of birth, although most studies had limited statistical power to detect differences for rare outcomes. Differences in location, context, quality and design of identified studies render results subject to variation. Conclusions and implications for practice: High-quality evidence about low-risk pregnancies indicates that place of birth had no statistically significant impact on infant mortality. The lower odds of maternal morbidity and obstetric intervention support the expansion of birth centre and home birth options for women with low-risk pregnancies.